The Augmented Educator: Decolonial Psychological Capital for EFL Teachers in the GenAI Era - Sahril Nur; Auliyanti Sahril Nurfadhilah; Muhammad Safar Nur (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2026)
The rapid integration of Generative Artificial Intelligence (GenAI) into higher education has raised new concerns for English as a Foreign Language (EFL) lecturers, particularly anxiety about professional value, pedagogical authority, and teacher identity. This explanatory sequential mixed-methods study examined how a culturally anchored professional development intervention could reduce AI-Induced Professional Anxiety (AIPA) and strengthen Teacher Psychological Capital (PsyCap). Twenty-five EFL lecturers who were also doctoral students participated in a 12-week Augmented Educator intervention grounded in Bugis-Makassar values: Sappa, Amaccang, and Siri' na Pacce. Quantitative data were collected using an adapted AIPA scale and a culturally adapted Teacher-PsyCap questionnaire, while qualitative data were drawn from reflective journals and interviews with eight participants. The findings showed a significant reduction in professional anxiety and notable gains in self-efficacy, resilience, hope, and optimism. The qualitative results further indicated that participants began to view AI not as a replacement for teachers, but as a tool requiring human judgment, cultural interpretation, and ethical guidance. The study argues that AI-related teacher development should move beyond technical training and include culturally meaningful psychological support for sustaining teacher agency in the GenAI era.